2020
DOI: 10.1177/0840470420950361
|View full text |Cite
|
Sign up to set email alerts
|

The ELIAS framework: A prescription for innovation and change

Abstract: Healthcare is a complex adaptive system with multiple stakeholders and dynamic environments. Therefore, healthcare organizations must continuously learn, innovate, adapt, and co-evolve to be successful. This article describes a systematic, comprehensive, and holistic performance management framework that healthcare managers can use to achieve these goals. The framework involves the ongoing assessment, modification, or replacement of current programs or services aimed at adapting successfully to achieve the org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Consistent with implementation science research on the use of evidence-informed theory and frameworks in intervention design, 29,[45][46][47] SFH ACTION was guided by the CNM and the SFH Framework. The former serving to reduce redundancy in the training of skill sets (QI, leadership, and SFH Framework) while providing a psychological environment encouraging collective action.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with implementation science research on the use of evidence-informed theory and frameworks in intervention design, 29,[45][46][47] SFH ACTION was guided by the CNM and the SFH Framework. The former serving to reduce redundancy in the training of skill sets (QI, leadership, and SFH Framework) while providing a psychological environment encouraging collective action.…”
Section: Discussionmentioning
confidence: 99%
“…The latter enabling teams to select and adapt improvements to best fit their hospital's context, reduce reactance to top-down control and maximize opportunity for innovation that may be particularly important in multi-hospital/ unit initiatives. 26,29 In linking these two features SFH ACTION may be unique amongst applications of CNM and multi-hospital interventions in the care of seniors. 46,47 Despite methodological limitations including non-random cohort assignment, reliance on subjective measures, and the absence of control groups, clinical outcome measures, or cost effectiveness data, results suggest that SFH ACTION achieved its objectives and can inform process improvement specialists, health system leaders, hospital administrators, and unit managers who are building more senior friendly hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frameworks such as the Enhances Learning, Innovation, Adaptation and Sustainability (ELIAS) framework, which was designed to guide the implementation process in healthcare organizations, can be used to inform the process. 5 Secondly, there is a need to reduce the time spent on the ward. Although the complexity of diabetes care is outside of the scope of this letter, data from this study showed that controls visited diabetes specialist clinic more frequently than cases.…”
Section: Indirect Costs Of Non-healing Diabetic Foot Wounds In An Afr...mentioning
confidence: 99%